PENGALOKASIAN DANA BANTUAN SOSIAL PROGRAM PAKET B: SEBUAH UPAYA PENINGKATAN KUALITAS PENDIDIKAN DASAR - Didik Suhardi (MAJALAH ILMIAH PEMBELAJARAN, 2012)
This research is performed to assess the advantages of Program Paket B in supporting efforts to improve the quality of basic education. Through the empowerment of the Program Paket B, learners are expected to become useful and helpful for the society and the state. In addition, the graduates of Program Paket B are also expected to continue their educations to the higher level as a way to improve Indonesian human resources. This research uses descriptive method with qualitative approach. The results show that the empowerment through the Program Paket B is quite fruitful in helping related government institution to improve the quality of basic education